STABILISASI TANAH LEMPUNG LUNAK MENGGUNAKAN KALSIT DAN RCC 15 DALAM PENINGKATAN NILAI CBR UNSOAKED - Rizky, Fahrul; Syahril, Syahril; Judiantono, Tonny; Shaputra, M Rio Eka (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2025)
Soft clay soil, which is often found in coastal and lowland areas of Indonesia, has characteristics such as low bearing capacity, high plasticity, and easy to subside under load, making it a challenge in infrastructure projects. Various soil stabilization methods have been developed, one of which is the use of chemical stabilizers. This study examines the use of Calcite (CaCO3) and Spent Catalyst RCC 15 as stabilization materials to improve the quality of soft clay soil. Calcite is known to reduce plasticity and increase soil bearing capacity, while Spent Catalyst RCC 15, as industrial waste, has the potential to improve soil structure and increase soil stability. Tests were conducted in the laboratory by mixing 6% Calcite and variations of Spent Catalyst RCC 15 (0%, 4%, and 8%) in soil samples from Cililin, West Java. The test results showed that the combination of Calcite and Spent Catalyst RCC 15 significantly increased the California Bearing Ratio (CBR) value of the soil, which means increasing the soil bearing capacity. The higher the percentage of Spent Catalyst RCC 15, the higher the CBR value obtained, indicating the effectiveness of this combination of stabilization materials in improving soft clay soil. These findings indicate the potential for an economical and sustainable solution to address soft clay soil problems in Indonesia and support more environmentally friendly industrial waste management.